RESEÑA de : Aguilera Añila, M.J.; Borderías Uribeondo, M.P.; González Yanci, M.P.; Santos Preciados, J.M. Geografía general I : geografía física. Madrid : UNED, 1989 - Muguruza Cañas, Carmen (Espacio Tiempo y Forma. Serie VI, Geografía, 1991)
-